Revolt in the desert: The famous seven pillars of wisdom condensed and rewritten - Lawrence, T E (Chandigarh The Browser: JGS Enterprises, 2024)
Revolt in the Desert is the most readable and condensed version of TE Lawrence$1 (Bs masterpiece Seven Pillars of Wisdom. Lawrence rewrote it because he found his earlier work cumbersome with many snap judgements that he had reason to regret. Better known as Lawrence of Arabia, his thrilling account vividly brings to life the daring guerrilla campaign he led during the Arab Revolt against the Ottoman Empire during World War I. The Arabs were loosely affiliated, tribal, and disunited at the time. Even the most senior Prince Faisal did not command uniform loyalty and was most firmly under the heel of the organized Turks of the Ottoman Empire. With the Turkish declaration of War against the Allies, the British set about seeing if they could raise ferment and revolt on the long desert flank of their enemy. They sent the then Lieutenant Lawrence, a bookish classist and archaeologist, but with knowledge of the area and the language of the Arabs, to be part of the British Mission. He suddenly found his element among the Arabs who were captivated by his dashing and inspired leadership as he led them from victory to victory over their oppressors. El Orens, as he was known to his men, became front-page news in England and around the world. Through Lieutenant-Colonel Lawrence$1 (Bs eyes, we journey across harsh desert landscapes, join in bold attacks on strategic towns, and delve into the complex politics and personalities of the Arab leaders and their forces. The book not only offers a glimpse into a pivotal moment in history but also introduces us to the enigmatic and visionary figure of Lawrence himself$1 (Boften pictured as a crank, genius, visionary, man (3z(Bgone native(3y(B, pawn, military leader, highly-strung, sensitive, and arrogant. His legacy continues to spark discussion and admiration.s
Keywords: Military; Motivational